Ethics as a true revolution, another way to read Levinas or beyond - Ulate, Esteban J. Beltrán; Timm de souza, Ricardo (Veritas (Porto Alegre), 2018)
This paper criticizes social revolution, by focusing on the reconfiguration of the notion from an ethical point of view. It is divided in three sections: (i) Brother’s death; (ii) Remove the sandals; (iii) Thou wilt be as many as the stars. Each section contains Levinas’s thought as the main axis. Although it is well known that Levinas does not develop a theory of revolution, it is possible to find a fruitful analysis in light of his meditations about politics and ethics. ***Ética como verdadeira revolução: Outra maneira de ler Levinas ou além*** Este artigo critica a revolução social, concentrando-se na reconfiguração da noção de um ponto de vista ético. Está dividido em três seções: (i) a morte do irmão; (ii) Remova as sandálias; (iii) Serás tantas quantas são as estrelas. Cada seção contém o pensamento de Levinas como o eixo principal. Embora seja bem sabido que Levinas não desenvolve uma teoria da revolução, é possível encontrar uma análise frutífera à luz de suas meditações sobre política e ética.